Pola Komunikasi Pasangan Perwira Badan Nasional Penanggulangan Terorisme Dalam Menjaga Perjanjian Moral Pada Pernikahan Jarak Jauh - Febiana Aura Annisa; Dina Kristina (STAI Bumi Silampari, 2026)
Long-distance marriage is a condition that requires emotional readiness, commitment, and effective communication patterns between husband and wife. This condition is commonly experienced by officer couples of the National Counterterrorism Agency (Badan Nasional Penanggulangan Terorisme/BNPT) as a consequence of official duties that involve high intensity and risk. From the beginning of marriage, BNPT officer couples have established a moral agreement that serves as a guideline in managing family life, particularly in facing physical separation due to distance. This study aims to examine the family communication patterns of BNPT officer couples in maintaining moral agreements within long-distance marriages. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation. The results show that The consensual pattern is reflected in open communication regarding important family matters and joint decision-making. Meanwhile, the protective pattern is evident in more controlled and selective communication, particularly related to compliance, attitudes, behavior, and their impact on the husband’s duties and career as an officer. Moral agreement is understood as an unwritten value-based mutual understanding that has been accepted since the beginning of marriage. This moral agreement shapes the way couples communicate, behave, and perform their respective roles within family life, especially while undergoing long-distance marital relationships.